The Effect of Religious Understanding of Islamic Education Students on Scientific Writing Ethics - Yulina Faoziah; Imam Mudjiono (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Religiosity is a benchmark for studying religion. In doing scientific work, students need to pay attention to the ethics of writing scientific papers. but some students do not understand writing and want an instant way to be able to quote sentences without including the author's name. This study aims to determine the level of influence of religiosity on the ethics of writing scientific papers for students of the 2017 Islamic Religious Education Study Program, Faculty of Islamic Studies, Islamic University of Indonesia. This type of research is field research with a quantitative approach. The object of this research is Religiosity (X) and Ethics of Scientific Writing (Y). In addition, this study used 41 random samples from 161 students, while to analyze the level of influence of religiosity on the ethics of scientific writing using simple linear regression analysis techniques. Based on the results of research and data analysis with simple linear regression analysis calculations, the results are the magnitude of the influence of religiosity R 0.573 obtained R Square of 0.328 or 32.8% and 67.2% influenced by other factors such as lack of socialization, poor understanding of scientific writing, lack of supervision, technological progress, student laziness, negative attitude so that it can be concluded that the influence of religiosity on the ethics of writing scientific papers for students of the 2017 Islamic Religious Education Study Program, Faculty of Islamic Studies, Islamic University of Indonesia by 32.8% is influenced by religiosity factors.